2013
DOI: 10.1371/journal.pone.0080434
|View full text |Cite
|
Sign up to set email alerts
|

Control of Directionality in Streptomyces Phage φBT1 Integrase-Mediated Site-Specific Recombination

Abstract: Streptomyces phage φBT1 integrates its genome into the attB site of the host chromosome with the attP site to generate attL and attR. The φBT1 integrase belongs to the large serine recombinase subfamily which directly binds to target sites to initiate double strand breakage and exchange. A recombination directionality factor (RDF) is commonly required for switching integration to excision. Here we report the characterization of the RDF protein for φBT1 recombination. The RDF, is a phage-encoded gp3 gene produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
35
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 40 publications
4
35
0
Order By: Relevance
“…PacBio thus offers a novel solution for studying the mechanism of phage tail fibre switching, and more generally, for the function of DNA invertase and other site-specific recombinases. For example, the DNA invertase gene has been severely truncated in the Phi4 prophage, suggesting that the inversion observed in this study must have been mediated by another enzyme in trans , as has been previously reported [49][51]. Notably, the Phi1 and Phi4 prophages encode near-identical 26 bp crossover sites at either end of their respective invertible segments (Table 3), suggesting that the Phi1 DNA invertase may be capable of mediating inversion at heterologous sites within the Phi4 prophage.…”
Section: Discussionsupporting
confidence: 78%
“…PacBio thus offers a novel solution for studying the mechanism of phage tail fibre switching, and more generally, for the function of DNA invertase and other site-specific recombinases. For example, the DNA invertase gene has been severely truncated in the Phi4 prophage, suggesting that the inversion observed in this study must have been mediated by another enzyme in trans , as has been previously reported [49][51]. Notably, the Phi1 and Phi4 prophages encode near-identical 26 bp crossover sites at either end of their respective invertible segments (Table 3), suggesting that the Phi1 DNA invertase may be capable of mediating inversion at heterologous sites within the Phi4 prophage.…”
Section: Discussionsupporting
confidence: 78%
“…S1 in the supplemental material), but they do not generate recombinant products presumably because the core (crossover) nucleotides are not complementary after odd numbers of subunit rotations, which prevents ligation. The ability of the RDF to enhance a more promiscuous reaction seems to be a general property of serine integrases, as it has been also documented in the Bxb1, Rv1, C31, and Bt1 systems (8,9,38). As elaborated below, the RDFs may remodel Int to both disrupt an inhibitory conformation and to directly promote specific synaptic complex architectures by orienting the trajectory of the CC motif.…”
Section: Discussionmentioning
confidence: 75%
“…1B). It is likely that Gp44 has additional roles in A118 biology, as has been described for other RDFs (9,(40)(41)(42).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations